Credit Risk Analysis of Indonesia Nickel Industry from Banking Financing Perspective - Setiawati, Linda; Anggono, Achmad Herlanto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
At the beginning of 2023, local banks observed increased demand for loan facilities to finance the purchase of new nickel transportation vessels, such as tugboats and barges. Loan repayments are expected to come from payments made by mining companies to shipping companies, underscoring the urgent need for a comprehensive credit risk analysis of Indonesia's nickel industry. Research found that market risk of nickel is highly influenced by China, the largest buyer, driven by demand from the stainless-steel industry and the rapidly expanding EV industry. Commodity risk analysis shows from 2018 to 2023, nickel prices exhibited annual volatility of 50% (0.50). A stress test indicated that if nickel prices dropped to USD 13,011.50/ton, companies would be unable to meet debt obligations. Financial risk analysis shows in year of 2022 both ANTM and INCO recorded good financial conditions with healthy profit margin and decent financial ratio including CR (above 1.0 times), DER (below 220%), and DSCR (above 1.0 times).